(untitled) (Asian Journal of Medical and Biological Research, 2019)
Repeat breeding reduces calf and milk production in crossbred cows. Serum lipid profiles in repeat breeding (RB) and normal cyclic (NC) cows were examined. Blood samples from 10 of each type cows were collected and TC, TG, HDL and LDL were estimated by spectrophotometer using enzymatic commercial kit. The serum TC in NC and RB were found within normal range (167.43 vs. 174.95mg/dl) (P>0.05). The TG in RB cows (121.92mg/dl) were significantly (P<0.05) higher than NC cows (115.03mg/dl). The HDL and LDL in NC (49.74 and 98.82mg/dl) and RB cows (46.40 and 103.09mg/dl) were found within normal range (P>0.05). Serum lipids have no effect on repeat breeding problem for crossbred cows. Asian J. Med. Biol. Res. June 2019, 5(2): 158-161